Identification and genetic characterization of astrovirus in wild boar (sus scrofa) in china - Fan-fan ZHANG; Yu-xin TANG; Yu YE; Nannan GUO; Min ZHANG; Hao LI; Dan LEI; Qiong WU; Dong-yan HUANG; De-ping SONG (Kafkas Universitesi Veteriner Fakültesi Dergisi, 2018)
Porcine astrovirus (PAstV) is a frequently detected virus in pigs suffering from diarrhea worldwide. Here, we report the first identification and complete genome sequence of astrovirus in wild boar (Sus scrofa) in Jiangxi, China. The complete genome sequence of a representative astrovirus, WBAstV/CH/2015, was amplified and determined. Sequence homology analysis showed that WBAstV/CH/2015 had 40.8% to 79.7% homology with PAstVs worlwide, and shared the highest homology (79.7%) with another wild boar astrovirus (WBAstV) strain WBAstV-1/2011/HUN from Hungary. Phylogenetic analysis showed that WBAstV/CH/2015 was closely related to WBAstV-1/2011/HUN and located in the cluster of PAstV 4.